Open Science, Open Data, and Open Scholarship: European Policies to Make Science Fit for the Twenty-First Century - Burgelman, Jean-Claude; Pascu, Corina; Szkuta, Katarzyna; Von Schomberg, Rene; Karalopoulos, Athanasios; Repanas, Konstantinos; Schouppe, Michel (Frontiers in Big Data, 2019)
Open science will make science more efficient, reliable and responsive to societal challenges. The European Commission has sought to advance Open Science policy from its inception in a holistic and integrated way, covering all aspects of the research cycle from scientific discovery and review to sharing knowledge, publishing and outreach. We present the steps taken with a forward-looking perspective of the challenges laying ahead, in particular the necessary change of the rewards and incentives system for researchers (for which various actors are co-responsible and which goes beyond the mandate the European Commission). Finally, we discuss the promising role of Artificial Intelligence within an Open Science perspective.